Analysis of the Influence of GDP and Open Unemployment Rate on Poverty Levels in Central Java Province - Tarigan, Andini; Buana, Bima Arya; Nababan, Dian Millennium; Putri, Devi Cahya; Hutasoit, Hosiana Febby; Manik, Lolona; Pakpahan, Mika Yohana; Nugrahadi, Eko Wahyu (Quantitative Economics Journal, 2023)
The high level of poverty in Central Java shows that the process of economic development has not been able to increase the welfare of society equally. Thus, an analysis is needed to determine the factors that influence poverty in order to overcome poverty. The purpose of this study is to analyze the gross regional domestic product (GRDP), the poverty level, the unemployment rate in the Central Java region. This study uses data from BPS with data on dependent and independent variables in the years 2001-2020. The analytical tool used in estimating the regression model is using the eviews application. The results showed that the GNP variable is negative and has a significant effect on poverty in Central Java, and the employment rate effect is positive and significant on poverty in Central Java.